2019
DOI: 10.3389/fncel.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in Neuropathologies Affecting the Frontal Cortex

Abstract: To an increasing extent, astrocytes are connected with various neuropathologies. Astrocytes comprise of a heterogeneous population of cells with region- and species-specific properties. The frontal cortex exhibits high levels of plasticity that is required for high cognitive functions and memory making this region especially susceptible to damage. Aberrations in the frontal cortex are involved with several cognitive disorders, including Alzheimer’s disease, Huntington’s disease and frontotemporal dementia. Hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 119 publications
0
19
0
2
Order By: Relevance
“…Besides their supportive role in terms of metabolism, astrocytes were shown to influence information processing and cognition by integrating local sensory information and behavioral state (Hallmann et al., 2017; Lima et al., 2014; Oksanen et al., 2019; Peteri et al., 2019; Slezak et al., 2019). In response to glucocorticoids, resetting of the circadian clock via non‐canonical pathways (Suchmanova et al., 2019) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their supportive role in terms of metabolism, astrocytes were shown to influence information processing and cognition by integrating local sensory information and behavioral state (Hallmann et al., 2017; Lima et al., 2014; Oksanen et al., 2019; Peteri et al., 2019; Slezak et al., 2019). In response to glucocorticoids, resetting of the circadian clock via non‐canonical pathways (Suchmanova et al., 2019) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important astrocytes function is to deliver energy to neurons by the astrocyte-neuron lactate shuttle (Bass et al, 1971; Sherwood et al, 2006). Astrocytes modulate Ca 2+ variations that influence neuronal activity releasing gliotransmitters (Peteri et al, 2019). The modulation of the neurotransmitter uptake involves the excitatory transporters 1 and 2 (EAAT1 and 2) (Roberts et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that occurrence of a traumatic event during adolescence [ 4 , 15 ], as well as developmental changes that occur during that stage [ 4 ], might increase the risk for PTSD and ADHD, where DA homeostasis has been shown to be altered [ 16 , 17 ]. Enhanced inflammatory conditions [ 18 ] and neurodegenerative hallmarks related to DAT alterations [ 19 , 20 , 21 ] are among the most relevant underlying mechanisms of aberrant PFC function in these disorders. Recent studies have also shown the important role played by astrocytes in the control of DA homeostasis in the PFC during early adolescence [ 13 , 19 ], when glutamatergic synapses in this area are at an important maturational stage [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%